Analisis Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kelurahan Se-Kecamatan Tulungagung - Sriyatin Sriyatin (Universitas Islam Kadiri, 2020)
Discussing employee performance will certainly not be separated from the factors that can affect a person's performance. Given that employee performance problems are very complex, the parties involved in an institution must be careful in observing the available resources. This research was conducted with the aim to determine the effect of work motivation and work environment on the performance of the employees of Kelurahan Se Tulungagung District, Tulungagung Regency. The method used in this research is a survey method. This research uses correlational techniques and this correlation study will use correlation and regression analysis. The results of the study are as follows: 1) Partial testing shows that work motivation has a positive and significant effect on employee performance. 2) Partial testing shows that the work environment has no positive and significant effect on employee performance. 3) Simultaneous testing shows that work motivation and work environment have a positive and significant effect on performance.